Relativistic calculations of K-, L- and M-shell X-ray production cross-sections by electron impact for Ne, Ar, Kr, Xe, Rn and Uuo. (October 2016) - Sampaio, J.M.; Madeira, T.I.; Guerra, M.; Parente, F.; Indelicato, P.; Santos, J.P.; Marques, J.P.
Abstract: In this work, we derive X-ray production cross-sections from electron-impact ionization cross-sections for Ne, Ar, Kr, Xe, Rn, and Uuo, calculated in the modified relativistic binary-encounter-Bethe model, and using as the only input parameter the binding energies obtained in the Dirac-Fock approach. Radiative and radiationless transition probabilities necessary to compute the inter- and intra-shell atomic yields were calculated in the same approach. Shell electron-impact ionization cross-sections and X-ray production cross-sections are compared with the corresponding cross-sections retrieved from the National Institute of Standards and Technology Reference Database and available experimental data. Abstract : Highlights: X-ray production cross-sections are calculated for several noble elements. Electron-Impact Ionization cross-sections are computed with the MRBEB model. Binding energies and atomic yields are obtained with the Dirac–Fock approach. Comparisons are made with other theoretical models and few available data. This approach is reliable in producing X-ray production cross-section data.